Do the types of subsidies and firms' heterogeneity affect the effectiveness of public R&D subsidies? Evidence from China's Innofund programme. Issue 3 (1st September 2016) - Xin, Fu; Zhang, Jie; Chen, Zhiyuan; Du, Xiaorong
Abstract : This paper aims to fill the gap in the extensive literature on the results of interaction between public and private R&D expenditures. Two types of public R&D subsidies, the appropriations and loan interest, are investigated in the effect of public subsidies by applying for a unique micro data set of Chinese manufacturing firms combined with the Innovation Fund for Small and Medium Technology-based Firms (Innofund). The results are consistent with the prediction that loan interest subsidies based on more competitive selective system are more effective for the public R&D subsidies than the appropriations. Firms' heterogeneity, measured by state-owned enterprises (SOEs) and private-owned enterprises (POEs), is tested for the different impact of public subsidies on corporate R&D investment. The results show that the crowding-in effect is mainly driven by POEs, not by SOEs, which confirms the theoretical assumption by Aghion and Tirole that the agency problem play a dominant role in corporate R&D activities. An improved econometric method, combined propensity score matching with difference-in-differences estimation strategy, is applied for correcting the selection bias. Our results are robust to different matching techniques.